1998
DOI: 10.1161/01.cir.97.22.2213
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasminogen Activator Inhibitor Type 1 in Coronary Artery Atherectomy Specimens From Type 2 Diabetic Compared With Nondiabetic Patients

Abstract: The disproportionate elevation of PAI-1 compared with u-PA observed in atheromatous material extracted from vessels of diabetic subjects is consistent with increased gene expression of PAI-1 in vessels as well as the known increase of PAI-1 in blood, presumably reflecting increased synthesis. The increased PAI-1 detected in the atheroma may contribute in vivo to accelerated or persistent thrombosis underlying acute occlusion and to vasculopathy exacerbated by clot-associated mitogens in the vessel wall. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(142 citation statements)
references
References 22 publications
7
130
0
5
Order By: Relevance
“…It has been reported that circulating levels of PAI-1 are increased in type 2 diabetic patients (27), and predict myocardial infarction (28,29). The plasma levels of PAI-1 antigen are reported to be increased in subjects with hypertension, dyslipidemia, and hyperinsulinemia (30).…”
Section: Plasma Levels Of Tpa Antigen and Pai-1 Antigenmentioning
confidence: 99%
“…It has been reported that circulating levels of PAI-1 are increased in type 2 diabetic patients (27), and predict myocardial infarction (28,29). The plasma levels of PAI-1 antigen are reported to be increased in subjects with hypertension, dyslipidemia, and hyperinsulinemia (30).…”
Section: Plasma Levels Of Tpa Antigen and Pai-1 Antigenmentioning
confidence: 99%
“…9,10 Expression of PAI-1 is increased in the vessel wall in patients with diabetes, a group particularly prone to exhibit restenosis. 11,12 In mice and other laboratory animals, increased arterial wall expression of PAI-1 has been found to promote increased neointimal cellularity after vascular injury. [13][14][15] By contrast, the cellular response to exogenous injury was significantly decreased after arterial injury in PAI-1-deficient mice.…”
mentioning
confidence: 99%
“…Increased PAI-1 has been implicated in both coronary arteries disease and venous thromboembolic events, by promoting plaque formation and venous thrombosis. [2,3,7,8] PAI-1 has also been shown to delay wound healing in vitro mostly through impairing angiogenesis and by inhibiting integrinvitronectin and vitronectin-vitronectin which are essential for cell migration and angiogenesis though activation of vascular endothelial growth factor receptor 2. [9][10][11] Our patient presents with multiple, chronic, non-healing wounds of varying locations and depths.…”
Section: Discussionmentioning
confidence: 99%